Contextual Teaching and Learning as a Social Learning Strategy for Strengthening Students’ Social Awareness in Higher Education - Retno Utari (Gema Cendekia Institute, 2026)
This article aims to conceptualize Contextual Teaching and Learning (CTL) as a social learning strategy for strengthening students’ social awareness in higher education. Using a conceptual literature review, this article synthesizes literature on CTL, social learning theory, student engagement, experiential learning, service-learning, transformative learning, and social awareness. The analysis shows that CTL has strategic pedagogical value because it connects academic knowledge with real-life contexts and enables students to interpret the social relevance of what they learn. When viewed through social learning theory, CTL is not merely a context-based instructional approach, but a socially situated learning strategy that facilitates observation, interaction, participation, reflection, and meaning-making. Student engagement functions as a mediating mechanism that links contextual learning experiences with changes in students’ understanding, attitudes, and social orientation. The article contributes an integrative conceptual framework that positions CTL as a pedagogical strategy for developing participation, empathy, social responsibility, and sensitivity toward community realities. This framework offers implications for curriculum design, pedagogical practice, and assessment in socially responsive higher education.